2010
DOI: 10.1186/1756-3305-3-46
|View full text |Cite
|
Sign up to set email alerts
|

The use of annual killifish in the biocontrol of the aquatic stages of mosquitoes in temporary bodies of fresh water; a potential new tool in vector control

Abstract: BackgroundMosquitoes that breed in temporary pools in remote areas that dry up seasonally are especially difficult to control through chemical or biological means. The annual killifish has been suggested as a means of eradicating the aquatic stages of mosquitoes in transient pools because they can maintain permanent populations in such habitats by undergoing suspended animation or diapause during the embryonic stages to survive periodic drought. However, very little is known about the predatory activity of ann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 23 publications
0
30
0
Order By: Relevance
“…When seasonal pools dry, the diapausing embryos survive in the dry substrate, and hatch at the start of the rains to re-populate the pools. As indicated by Matias and Adrias (2010), this life cycle which coincides with that of their potential prey such as mosquitoes that also begin their life cycle in the same seasonal pools provides a compelling reason for the interest in the potential of killifish for vector control in seasonal habitats.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations
“…When seasonal pools dry, the diapausing embryos survive in the dry substrate, and hatch at the start of the rains to re-populate the pools. As indicated by Matias and Adrias (2010), this life cycle which coincides with that of their potential prey such as mosquitoes that also begin their life cycle in the same seasonal pools provides a compelling reason for the interest in the potential of killifish for vector control in seasonal habitats.…”
Section: Introductionmentioning
confidence: 95%
“…Regardless of this growing interest, few studies have looked at the prospects of some killifish for this purpose in Africa (Ghosh et al 2004;Howard et al 2007), with the well explored ones being species of the genus Nothobranchius common in Tanzania (Matias and Adrias 2010). However, there are other species that have a wider geographical distribution on the continent that may also be suitable candidates in the localities where they occur, but have remained unexplored.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Ghosh et al (2011) indicated that the important of using surface feeding predators like Poecilia reticulata and Gambusia affinis in chikungunya vector control programs. Further the patentability of annual killifish, Nothobranchius guentheri on mosquito control in temporary water bodies was proposed by Matias and Adrias (2010) due to surface living and insectivore nature of these fishes.…”
Section: Insect Larvae Unidentified Insects Hymenopteramentioning
confidence: 99%